Moderasi Beragama dan Inovasi Pembelajaran di Pasraman Lombok Tengah - Ni Made Arini (Universitas Hamzanwadi, 2024)
Nonformal Pasraman, as a Hindu religious educational institution, plays a crucial role in enhancing the faith and devotion of Hindu adherents. However, it faces various challenges that impact the quality of learning. This study analyzes the implementation and development of religious moderation values in the curriculum and materials of Pasraman, the role of Pasraman in implementing moderation, and the potential development of Hindu-based learning models. The research employs a qualitative descriptive approach, utilizing data from observations, interviews, and documentation from all Pasraman in Central Lombok. The data were reduced, displayed, and verificated narratively. The findings indicate that religious moderation values in Pasraman are indirectly taught through Hindu teachings such as Dharma, Tat Twam Asi, and Tri Hita Karana, which support the role of Pasraman in moderation. This role is further strengthened through the optimal application of the Tri Kaya Parisudha teachings by the acaryas. Pasraman possesses advantages in terms of demography, foundation licenses, and Hindu teachings that support character formation. However, it also faces weaknesses, such as limited teaching staff, facilities, and management. Potential development includes the provision of teaching materials, learning methods, and the establishment of district-level organizations as discussion forums.